Disclosure in the quarterly reports of Malaysian companies - Ku Ismail, Ku Nor Izah; Chandler, Roy (Curtin Business School, 2005)
This study examined the extent of disclosure in the quarterly reports of Malaysian listed companies.The quarterly reports of 117 companies ended on 30 September 2001 were the subjects of the study.First, this study observed companies’ overall disclosure with respect to the Listing Requirements of the KLSE.Second, it observed the extent of narrative disclosure with respect to comments on material changes,review of performance and comment on current year prospects.Finally, the extent of disclosure was tested for association with profitability, growth and leverage of a company.Generally, companies disclose all the mandatory financial statements and relevant notes to the accounts.However, the extent of mandatory narrative disclosures varies.Generally, companies appear to provide a minimum level of disclosure.This study reveals that the extent of disclosure is positively associated with the leverage of a company.No significant association was evidenced between the extent of disclosure and profitability and growth of a company.Plausible explanations of the findings are provided in this paper.The findings provide some useful insights to users, preparers and policy makers into the current practice of reporting selected narrative disclosure in the quarterly reports.